Grounded theory a practical guide - Birks, Melanie (SAGE, 2011)
This is a highly practical book which introduces the whole range of grounded theory approaches. Unlike most existing books in this area, which are written from a particular philosophical standpoint, this text provides a comprehensive description of the strategies and techniques employed in this methodology.